Ruin probabilities for risk models with constant interest - Nguyen, Huy Hoang (Ukrains’kyi Matematychnyi Zhurnal, 2026)
UDC 519.21 We consider continuous-time risk models with m-dependent claim sizes and constant interest rate. Under some special conditions, we obtain the upper bound for the infinite-time ruin probability. Our approach is based on the martingale methods.